2014
DOI: 10.1017/s136898001400127x
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of shopper experiences at an urban farmers’ market using the Stanford Healthy Neighborhood Discovery Tool

Abstract: Objective To understand factors which enhance or detract from farmers’ market shopper experiences to inform targeted interventions to increase farmers’ market utilization, community-building and social marketing strategies. Design A consumer-intercept study using the Stanford Healthy Neighborhood Discovery Tool to capture real-time perceptions via photographs and audio narratives. Setting An urban farmers’ market in a large metropolitan US city. Participants Thirty-eight farmers’ market shoppers, who rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…This approach previously has been successfully pilot tested in diverse locations in the USA, including in lowincome Latino neighborhoods. [20][21][22][23][24] However, it has never been pilot tested in a lowor middle-income country such as Mexico. Low-and middle-income countries are high priorities for physical activity promotion because of increasing levels of physical inactivity, obesity, and the high burden of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This approach previously has been successfully pilot tested in diverse locations in the USA, including in lowincome Latino neighborhoods. [20][21][22][23][24] However, it has never been pilot tested in a lowor middle-income country such as Mexico. Low-and middle-income countries are high priorities for physical activity promotion because of increasing levels of physical inactivity, obesity, and the high burden of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The target sample size was 30 adults aged 45 years and older (8 to 11 per census tract) to achieve saturation of the neighborhood information provided, as seen in US-based studies. [20][21][22][23][24] In these latter studies, it was found that Bsaturation^in relation to basic neighborhood environment issues being identified could be achieved with approximately 8-10 residents from a neighborhood. We also aimed to include a smaller total sample of 10 adolescents ages 11 to 14 years (4 to 5 adolescents per census tract) to complement the information obtained from the adults.…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations